Student Burnout Prevention: Innovative Counseling Management Strategies - Hasan Baharun; Siti Nur Halisoh; Zohaib Hassan Sain (Institut Agama Islam An-Nawawi Purworejo, 2024)
This study explores how counselling service management can overcome burnout in students in madrasas. This study uses a qualitative approach with a case study method to understand the effectiveness of counselling services in the school. The research method used is a qualitative method of case studies. Data were collected through in-depth interviews, participatory observations, and documentation studies involving students, counsellors, and teachers. Data analysis uses thematic analysis techniques to identify the main themes that emerge from the data. The results show that an in-depth process of identifying student needs can reduce the risk of burnout by designing more appropriate interventions. The appointment of the right counsellor increases the effectiveness of counselling services through a better understanding of student problems. Ongoing mentoring programs provide emotional and practical support that helps students develop better-coping strategies. In addition, student feedback is used to improve the quality of counselling services. This research contributes significantly by updating the perspective on counselling service management and offering intervention models that can be applied in various educational institutions to overcome burnout. These findings provide practical guidance for other educational institutions to improve their counselling services to address student burnout.